KKN TEMATIK UMSU DALAM EDUKASI ANTI BULLYING & KEGIATAN ECOPRINT DI DESA SUKA MAKMUR - Nurmayasari Nurmayasari; Andryana, Noer Djanius Sahfitri, Ela Safitri, Edisah Putra Nainggolan (Adiba Aisha Amira, 2024)
The purpose of Thematic KKN is to find out Anti Bullying Education & Ecoprint Activities in Suka Makmur Village, The Research Method In implementing the UMSU Thematic KKN in Suka Makmur Village, the research used a descriptive qualitative approach to understand the phenomenon of bullying and the potential for ecoprint development in the community. This method was chosen because it is able to describe in depth the social conditions and dynamics of the village community through direct observation, interviews, and documentation of activities. This research also applied the Participatory Action Research (PAR) method, which involves the active participation of villagers. Overall, the UMSU Thematic KKN in Suka Makmur Village successfully touched on two important aspects of children's education: bullying prevention and environmental preservation. Through the anti-bullying education program, students not only provide knowledge but also build positive character in students. Meanwhile, the ecoprinting activity enriches students' learning experience with practical skills that can enhance their creativity. With this innovative and participatory approach, it is hoped that the younger generation can grow into individuals who care more about themselves, others, and the environment around them.